Urologic surgery and invasive procedures during coronavirus pandemic: Retrospective comparison of risk infection in a referral Covid hospital and in a free-Covid hospital - Antonio Maria, Granata (Urologia, 2020)
INTRODUCTION: On 21 February 2020, ‘Luigi Sacco’ Hospital was identified as a Covid-19 referral Hospital in Lombardy. The Department of Urology of our Healthcare Institution consists of two Urology Units, one at ‘L.Sacco’ Hospital (hereinafter referred to as Covid-19 hospital) and one at ‘Fatebenefratelli’ Hospital (hereinafter referred to as Covid-19-free hospital). The Healthcare System’s Administration communicated to all personnel the implementation of a planned ‘biological risk protocol’ at the Covid-19 hospital, while the Covid-19-free hospital followed regular government recommendations. We evaluated the risk of Sars-Cov-2 infection in the patients treated for surgical or invasive urologic procedures during the epidemic in the two different hospitals. MATERIALS AND METHODS: At the Covid-19 hospital, 12 patients underwent surgery and 51 patients invasive diagnostic procedures between 22 February and 8 March 2020; in the same period, at the Covid-19-free hospital, 21 patients underwent surgery and 56 patients invasive diagnostic procedures. We compared the incidence of Sars-Cov-2 infection among the patients who were accessed in the two Urology Units in the period of different restrictive measures after the outbreak of the epidemic. RESULTS: We registered no cases of Sars-Cov-2 infection in the patients hospitalized in that period in Covid-19 hospital, despite three cases of swab positivity in the Covid-19-free hospital. CONCLUSION: The early implementation of extraordinary measures to restrict the spread of the virus offers a good protection also in a Covid-19 referral Hospital. The adoption of safety measures may be considered even after the end of the pandemic in all the health systems.